2021
DOI: 10.1039/d0ob02249g
|View full text |Cite
|
Sign up to set email alerts
|

A versatile stereocontrolled synthesis of 2-deoxyiminosugar C-glycosides and their evaluation as glycosidase inhibitors

Abstract: Dihydroxylation of (R,S) or (S,S)-2,6-disubstituted dehydropiperidines enantioselectively obtained from stannylated precursors allows a versatile preparation of 2-deoxyiminosugar C-glycosides which have been evaluated as glycosidases inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…It is well‐known that the glycosidic linkages in carbohydrate immunogens are susceptible to in vivo degradation by glycoside hydrolases, thus using antigenic carbohydrate analogs that are more resistant to enzymatic hydrolysis [15–20] have been considered as a viable strategy, as using stable synthetic analogs of such classes would ensure the integrity of the carbohydrate antigens during immunization thus the raised antibodies are more consistent to the structures of intact antigens. Two exemplary approaches have been reported by replacing the glycosidic oxygen(s) of the native carbohydrate antigens with a sulfur or carbon atom to generate the corresponding enzyme‐resistant S ‐glycosides [21–28] or C ‐glycosides [29–33] . For S ‐glycosides, studies have shown that although the C−S single bond is longer than the C−O bond, the C−S−C bond angle is significantly smaller than the C−O−C angle, which often results in very little differences between the position of the carbon atoms of the two types of glycosidic linkages; [34–40] studies have also shown that while S ‐glycosides are more flexible about the glycosidic linkage, they do sample similar conformational space of their O ‐glycoside counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well‐known that the glycosidic linkages in carbohydrate immunogens are susceptible to in vivo degradation by glycoside hydrolases, thus using antigenic carbohydrate analogs that are more resistant to enzymatic hydrolysis [15–20] have been considered as a viable strategy, as using stable synthetic analogs of such classes would ensure the integrity of the carbohydrate antigens during immunization thus the raised antibodies are more consistent to the structures of intact antigens. Two exemplary approaches have been reported by replacing the glycosidic oxygen(s) of the native carbohydrate antigens with a sulfur or carbon atom to generate the corresponding enzyme‐resistant S ‐glycosides [21–28] or C ‐glycosides [29–33] . For S ‐glycosides, studies have shown that although the C−S single bond is longer than the C−O bond, the C−S−C bond angle is significantly smaller than the C−O−C angle, which often results in very little differences between the position of the carbon atoms of the two types of glycosidic linkages; [34–40] studies have also shown that while S ‐glycosides are more flexible about the glycosidic linkage, they do sample similar conformational space of their O ‐glycoside counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Two exemplary approaches have been reported by replacing the glycosidic oxygen(s) of the native carbohydrate antigens with a sulfur or carbon atom to generate the corresponding enzyme-resistant S-glycosides [21][22][23][24][25][26][27][28] or C-glycosides. [29][30][31][32][33] For S-glycosides, studies have shown that although the CÀ S single bond is longer than the CÀ O bond, the CÀ SÀ C bond angle is significantly smaller than the CÀ OÀ C angle, which often results in very little differences between the position of the carbon atoms of the two types of glycosidic linkages; [34][35][36][37][38][39][40] studies have also shown that while S-glycosides are more flexible about the glycosidic linkage, they do sample similar conformational space of their O-glycoside counterparts. Thus geometrically, S-glycosides can effectively mimic their native O-glycosides when used as an antigen.…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic instability of aminoacetal functionalities makes impractical the synthesis of iminosugar O -glycosides or of analogues having other heteroatom substituents at the pseudoanomeric position. Instead, aglycon-like appendages have been incorporated through N -substitution and C -branching approaches, which accounts for the two major subclasses of iminosugar derivatives on record.…”
Section: Introductionmentioning
confidence: 99%